(untitled) (Bangladesh Medical Journal Khulna, 2016)
The aim of our study is exploring the safety and feasibility of nondescent vaginal hysterectomy in benign diseases of uterus and also maximizing the proportion of hysterectomy performed vaginally. This was a prospective descriptive study done in obstetrics and gynaecology department of Khulna medical college hospital and two private clinic in Khulna and Satkhira. Over a period of 3 years from January 2012 to December 2014, a total of 56 cases underwent hysterectomy done vaginally for benign diseases. The most common age group affected was 41-50 years (64.28%) and second common group was below 40 years. Majority (73.21%) of the patients was multiparas and 6 weeks size affected uterus was 41.07%. Most common indication for NDVH was dysfiinctional uterine bleeding (39.29%) and fibroid uterus was 35.71%. Among 56 patients 25 cases needed dcbulking technique (44.64%) of which bisection was 32.14%. Maximum (53.57%) operation was completed within 61 to 90 minutes. Maximum blood loss of 201 ml or more was in 3 cases but only 5 patients needed blood transfusion. Among 56 patients. 5 (8.92%) patients suffered from various forms of complications but urinary fistula was nil. So it can be concluded that non descent vaginal hysterectomy has many advantages which include short hospital stay and fast convalescence. Bang Med J (Khulna) 2015; 48 : 16-19